2021
DOI: 10.7759/cureus.16276
|View full text |Cite
|
Sign up to set email alerts
|

Role of Uterine Artery Doppler Ultrasound in Predicting Pre-Eclampsia in High-Risk Women

Abstract: Background and objectivePre-eclampsia (PE) is a major cause of maternal morbidity and mortality. The utility of Doppler ultrasonography (U/S) in predicting PE has not been extensively explored. This study aimed to determine the role of Doppler U/S in predicting PE among high-risk women. MethodologyThis was a retrospective observational study conducted at the Department of Obstetrics and Gynecology of Abbasi Shaheed Hospital in Karachi, over a period of one year, from January 2019 till December 2019. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
(18 reference statements)
1
4
1
1
Order By: Relevance
“…The E / e value of the Norm group was higher than that of the Ctrl group ( P < 0.05). These results suggested that the left ventricular systolic function of women during normal pregnancy had no significant change compared with nonpregnant women of reproductive age, which was different from the results of Shahid et al [ 19 ]. The gestational age of the included pregnant women was relatively small, and the left ventricular systolic function was in a compensated phase, so there was no significant difference compared with nonpregnant women of reproductive age.…”
Section: Discussioncontrasting
confidence: 92%
“…The E / e value of the Norm group was higher than that of the Ctrl group ( P < 0.05). These results suggested that the left ventricular systolic function of women during normal pregnancy had no significant change compared with nonpregnant women of reproductive age, which was different from the results of Shahid et al [ 19 ]. The gestational age of the included pregnant women was relatively small, and the left ventricular systolic function was in a compensated phase, so there was no significant difference compared with nonpregnant women of reproductive age.…”
Section: Discussioncontrasting
confidence: 92%
“…Otro estudio indica que los índices Doppler individuales fueron los más sensibles con un 71% mientras que la presencia de una muesca en la arteria uterina (unilateral/bilateral) fue la más específica para predicción de PE, siendo la sensibilidad más baja la del IR bilateral con un 41% (63).…”
Section: Discussionunclassified
“…However, other studies have reported increased wall and tunica media thickness and an increase in the wall-luminal ratio [53]; therefore, more studies analysing these structural changes are needed. The utility of Doppler ultrasonography in predicting pre-eclampsia has not been extensively studied [75]. However, some studies show that abnormal Doppler ultrasonography has good overall sensitivity in predicting pre-eclampsia [75].…”
Section: Hypertensive Disorders During Pregnancymentioning
confidence: 99%
“…The utility of Doppler ultrasonography in predicting pre-eclampsia has not been extensively studied [75]. However, some studies show that abnormal Doppler ultrasonography has good overall sensitivity in predicting pre-eclampsia [75]. Some studies have also found relationships of preeclampsia with hypercoiling, marginal and paramarginal insertion, and SUA [73].…”
Section: Hypertensive Disorders During Pregnancymentioning
confidence: 99%